An improved mathematical model for assessing the performance of the SDHW systems - Khatib, imad; Awad, Moh’d; osaily, kazem (International Journal of Engineering (IJE), Volume(3):Issue(6), 2009)
Short term testing of the SDHW system components is an essential prerequisite for assessing the system’s long-term thermal performance. Relevant performance parameters are therefore, crucial in recommending systems outputs and feasibility. Short term testing methods based on ANSI/ASHRAE and ISO standards testing methods and the mathematical system energy input/output models used showed sensitivity to variation of the day length used in testing and to different levels of irradiance. On the bases of the thermal performance testing carried out for a SDHW system and the outcomes of the day-by-day long-term performance prediction, a new mathematical system energy model is proposed which may reduce the number of tests required, minimizes the dependency on the day length and the sensitivity of the levels of irradiance.
Keywords: SDHW Systems, Performance Testing, Long-Term Performance Prediction, Energy Input/output System Equation model.